2022
DOI: 10.1155/2022/5477432
|View full text |Cite|
|
Sign up to set email alerts
|

Carbetocin Controls Intraoperative Blood Loss and Thickness of Myometrium in Scar Uterus Cases

Abstract: Objective. To study the effect of carbetocin on intraoperative blood loss and thickness of myometrium during cesarean section with the scarred uterus at term pregnancy. Methods. Pregnant women with full-term gestational scar uterus who underwent cesarean section from March 1, 2021, to April 30, 2022, were retrospectively collected and divided into a reference group (using oxytocin) or a study group (using carbetocin). The clinical data of the two groups were retrospectively analyzed, and the operation time, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Our study was consistent with Sun et al, 2022 (22) who aimed to study the efficacy of carbetocin on blood loss during surgery and diameter of myometrium during CS with the uterus with previous scare at term pregnancy and difference in stay of hospital, as a statistic significance different on the studied groups on a hospital stay (Pvalue: = 0.006).…”
Section: Al Anwar Et Al (2022)supporting
confidence: 91%
“…Our study was consistent with Sun et al, 2022 (22) who aimed to study the efficacy of carbetocin on blood loss during surgery and diameter of myometrium during CS with the uterus with previous scare at term pregnancy and difference in stay of hospital, as a statistic significance different on the studied groups on a hospital stay (Pvalue: = 0.006).…”
Section: Al Anwar Et Al (2022)supporting
confidence: 91%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%